Sinus Hemodynamics Variation with Tilted Transcatheter Aortic Valve Deployments - Hatoum, Hoda (Ann Biomed Eng, 2018)
Leaflet thrombosis is a complication associated with transcatheter aortic valve(TAV) replacement(TAVR) correlated with sinus flow stasis. Sinus hemodynamics are important because they dictate shear stress and washout necessary to avoid stasis on TAV leaflets. Sinus flow is controlled by TAV axial deployment position but little is known regarding TAV axis misalignment effect. This study aims to elucidate TAV angular misalignment with respect to aortic root axis effect on sinus flow stasis potentially leading to leaflet thrombosis. Sinus hemodynamics were assessed in-vitro using particle-image velocimetry in three different angular misalignments with respect to aorta axis: untilted, tilted away from the sinus and tilted towards sinus. A 26mm Edwards SAPIEN3 was implanted in a 3D printed model of an anatomically realistic aortic root. TAV hemodynamics, sinus vortex tracking, leaflet shear stress probability density functions, and sinus blood time to washout were calculated. While pressure gradients differed insignificantly, blood velocity and vorticity decreased significantly in both tilted cases sinuses. Shear stress probability near the leaflet decreases with tilt indicating stasis. TAV tilted away from the sinus is the most unfavorable scenario with poor washout. TAV axial misalignment adds to factors list that could influence leaflet thrombosis risk through modifying sinus hemodynamics and washout.